Reactivation of the Epicardium at the Origin of Myocardial Fibro-Fatty Infiltration During the Atrial Cardiomyopathy. Issue 10 (8th May 2020) - Suffee, Nadine; Moore-Morris, Thomas; Jagla, Bernd; Mougenot, Nathalie; Dilanian, Gilles; Berthet, Myriam; Proukhnitzky, Julie; Le Prince, Pascal; Tregouet, David A.; Pucéat, Michel; Hatem, Stéphane N.
Abstract : Rationale: Fibro-fatty infiltration of subepicardial layers of the atrial wall has been shown to contribute to the substrate of atrial fibrillation. Objective: Here, we examined if the epicardium that contains multipotent cells is involved in this remodeling process. Methods and Results: One hundred nine human surgical right atrial specimens were evaluated. There was a relatively greater extent of epicardial thickening and dense fibro-fatty infiltrates in atrial tissue sections from patients aged over 70 years who had mitral valve disease or atrial fibrillation when compared with patients aged less than 70 years with ischemic cardiomyopathy as indicated using logistic regression adjusted for age and gender. Cells coexpressing markers of epicardial progenitors and fibroblasts were detected in fibro-fatty infiltrates. Such epicardial remodeling was reproduced in an experimental model of atrial cardiomyopathy in rat and in Wilms tumor 1 (WT1) CreERT2/+ ;ROSA-tdT +/− mice. In the latter, genetic lineage tracing demonstrated the epicardial origin of fibroblasts within fibro-fatty infiltrates. A subpopulation of human adult epicardial-derived cells expressing PDGFR (platelet-derived growth factor receptor)-α were isolated and differentiated into myofibroblasts in the presence of Ang II (angiotensin II). Furthermore, single-cell RNA-sequencing analysis identified several clusters of adult epicardial-derived cells and revealed their specification from adipogenic to fibrogenic cells in the rat model of atrial cardiomyopathy. Conclusions: Epicardium is reactivated during the formation of the atrial cardiomyopathy. Subsets of adult epicardial-derived cells, preprogrammed towards a specific cell fate, contribute to fibro-fatty infiltration of subepicardium of diseased atria. Our study reveals the biological basis for chronic atrial myocardial remodeling that paves the way of atrial fibrillation. Abstract : Supplemental Digital Content is available in the text.